3‐iodothyroacetic acid, a metabolite of thyroid hormone, induces itch and reduces threshold to noxious and to painful heat stimuli in mice. (23rd January 2015) - Laurino, Annunziatina; De Siena, Gaetano; Resta, Francesco; Masi, Alessio; Musilli, Claudia; Zucchi, Riccardo; Raimondi, Laura
Abstract : Background and purpose: Itch is associated with increased sensitization to nociceptive stimuli. We investigated whether 3‐iodothyroacetic acid (TA1), by releasing histamine, induces itch and increases sensitization to noxious and painful heat stimuli. Experimental Approach: Itch was evaluated after s.c. administration of TA1 (0.4, 1.32 and 4 μg·kg −1 ). Mice threshold to noxious (NHT) and to painful heat stimuli were evaluated by the increasing‐temperature hot plate (from 45.5 to 49.5°C) or by the hot plate (51.5°C) test, respectively, 15 min after i.p. injection of TA1 (0.4, 1.32 and 4 μg·kg −1 ). Itch, NHT and pain threshold evaluation were repeated in mice pretreated with pyrilamine. Itch and NHT were also measured in HDC +/+ and HDC −/− following injection of saline or TA1 (1.32, 4 and 11 μg·kg −1 ; s.c. and i.p.). pERK1/2 levels were determined by Western blot in dorsal root ganglia (DRG) isolated from CD1 mice 15 min after they received (i.p.): saline, saline and noxious heat stimulus (46.5°C), TA1 (0.1, 0.4, 1.32, 4 μg·kg −1 ) or TA1 1.32 μg·kg −1 and noxious heat stimulus. Key Results: TA1 0.4 and 1.32 μg·kg −1 induced itch and reduced NHT; pyrilamine pretreatment prevented both of these effects. TA1 4 μg·kg −1 (i.p.) reduced pain threshold without inducing itch or modifying NHT. In HDC −/− mice, TA1 failed to induce itch and to reduce NHT. In DRG, pERK1/2 levels were significantly increased by noxious heat stimuli and by TA1 0.1, 0.4 and 1.32 μg·kg −1 ; i.p. Conclusions and Implications: Increased TA1 levels induce itch and an enhanced sensitivity to noxious heat stimuli suggesting that TA1 might represent a potential cause of itch in thyroid diseases.